The moderating effects of perceived social worth and organizational virtuousness on the relationship between emotional labor, precarious work, and organizational commitment among ASHA workers in India - N, Akbar Jan; David, Rajasekhar; A. K., Subramani; Singh, Sharda; Nigoti, Utkarsh (Acta psychologica, 2024)
Accredited Social Health Activists (ASHAs) in India are the subjects of this study, which explores the complex relationships between emotional labor (EL) and unstable work environments and how these relationships affect organizational commitment (OC). The study also looked at how organizational virtuousness (OV) and perceived social value mediated the relationship between precarious work (PW), EL, and OC. This study included a total sample size of N = 467 ASHA personnel from a variety of healthcare settings. Hierarchical regression analysis was used to look at the moderating effects using the Hayes Process Macro. The findings suggest that there are noteworthy negative associations between EL, PW, and the OC of ASHA workers. Nevertheless, OV and perceived social worth (PSW) emerged as significant moderators. More precisely, elevated levels of PSW and OV mitigated the adverse effects of PW and EL on the OC of ASHA workers.